The Multiplayer Classroom: Designing Coursework as a Game - Sheldon, Lee (Taylor & Francis Group, 2020)
Go beyond gamification’s badges and leaderboards with the new edition of the book, first published in 2011, that helped transform education. Going far beyond the first edition of The Multiplayer Classroom, forthrightly examining what worked and what didn’t over years of development, here are the tools to design any structured learning experience as a game to engage your students, raise their grades, and ensure their attendance. Suitable for use in the classroom or the boardroom, this book features a reader-friendly style that introduces game concepts and vocabulary in a logical way. Also included are case studies, both past and present, from others teaching in their own multiplayer classrooms around the world. You don't need any experience making games or even playing games to use this book. You don’t even need a computer. Yet, you will join many hundreds of educators who have learned how to create multiplayer games for any age on any subject.